ANALISIS PENGARUH NILAI-NILAI BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Sumarhadi Sumarhadi (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Bureaucratic reform is not a word, but a demand for goodness. In fact, government agencies work under an oath for the benefit of the state, namely serving the life of the Indonesian people. Therefore, the study of civil servants is part of supervision, to maintain the quality of good governance. This study aims to examine and analyze how cultural values ??can be used as a reinforcing measure for employee performance. To prove this, a scientific study with a quantitative approach was conducted. A study that is oriented to expressing the real condition of a phenomenon by presenting statistical data, so that it is easier to understand. The results of the study suggest that cultural values ??are proven to strengthen employee performance, especially professional attitudes. This confirms that performance is closer to a professional attitude, so that when professional values ??are reinforced, it can directly improve the quality of work. This fact is a recommendation to the agency, to improve employee performance, it is better to pay special attention to professional values